Piston control for an Integral Compression Wind Turbine - Woolhead, Simon (2015)
This thesis concerns an analysis of an Integral Compressed Air Wind Turbine (ICWT), in which energy is extracted from a slow-moving renewable source through the use of compressed air. This concept is particularly applicable to large offshore wind turbines, and can be readily integrated with compressed air energy storage methods. The ICWT has a very large rotor with free pistons travelling within the rotor blades, inducting and compressing air to high pressures at each end of the stroke. The compressed air can be stored and expanded when the energy is required, solving the intermittency issue of wind energy. By gathering energy along the rotor blades, rather than at the hub, it also avoids the very high torques associated with extremely large turbines.